Coupling picodroplet microfluidics with plate imaging for the rapid creation of biomanufacturing suitable cell lines with high probability and improved multi‐step assurance of monoclonality. Issue 1 (25th October 2021) - Pybus, Leon P.; Kalsi, Devika; Matthews, Joe T.; Hawke, Ellie; Barber, Nicholas; Richer, Rachel; Young, Alison; Saunders, Fay L.
Abstract: Background: There is an expectation from regulatory agencies that cell lines used in the commercial production of biopharmaceuticals are derived from a single cell progenitor. Traditional methods of single cell cloning include the use of the limiting dilution cloning method which often requires multiple rounds of low cell density cell plating and either microscopic evaluation that wells contain single cells and/or the calculation of a statistically derived probability of monoclonality. Methods and Results: We have combined the single cell screening, deposition and picodroplet imaging ability of Sphere Fluidics' Cyto‐Mine technology with the plate imaging capability of the Solentim Cell Metric to create a novel workflow for the generation of high producing clonal cell lines with both high probability and assurance of monoclonality. The efficiency of three key stages of the process (single cell picodroplet encapsulation, single picodroplet dispensation and single cell settling in the focal plane of the plate imager) was determined and a probability calculation was derived using the Wilson Score Interval method. The combined probability that a single cell is encapsulated into a picodroplet, is deposited into the correct well of a 96‐well plate and that a cell settles into the focal plane of the plate imager yields a combined > 99% probability of monoclonality. Furthermore, visual verification of a single cell progenitor is obtained at multiple steps throughout the cloning workflow. Conclusion: This novel methodology for the rapid creation of high quality clonal cell lines for biomanufacturing purposes has many advantages over more traditional approaches including improved assurance of single cell derivation, integrated imaging capability, assay flexibility, equipment utilization time and in‐process cell line segregation. Graphical Abstract and Lay Summary: There is an expectation from regulatory agencies that cell lines used in the commercial production of biopharmaceuticals are derived from a single cell progenitor. Traditional methods of single cell cloning include the use of the limiting dilution cloning method which often requires multiple rounds of low cell density cell plating and either microscopic evaluation that wells contain single cells and/or the calculation of a statistically derived probability of monoclonality. We have combined the single cell screening, deposition and picodroplet imaging ability of Sphere Fluidics' Cyto‐Mine technology with the plate imaging capability of the Solentim Cell Metric to create a novel workflow for the generation of high producing clonal cell lines with both high probability and assurance of monoclonality.